Microdosimetry in 3D realistic mitochondria phantoms: Geant4 Monte Carlo tracking of 250 keV photons in phantoms reconstructed from microscopic images. (October 2017) - Zein, S.; Francis, Z.; Montarou, G.; Chandez, F.; Kane, M.S.; Chevrollier, A.
Highlights: 3D realistic phantom of human fibroblast mitochondria is produced. The realistic phantom is successfully imported into Geant4 as a tetrahedral mesh. The phantom describes the complexity of the mitochondria structure. Tracking of 250 keV photons is performed. Microdosimetric quantities are calculated inside the phantom. Abstract: Mitochondria are considered to be sensitive radiation targets since they control processes vital to the cell's functioning. These organelles are starting to get attention and some studies are investigating the radiation dose inside them. In previous studies, mitochondria are represented as simple ellipsoids inside the cell not taking into consideration the complexity of their shape. In this study, realistic phantoms are built based on deconvolved widefield fluorescent microscopic images of the mitochondrial networks of fibroblast cells. The phantoms are imported into Geant4 as tessellated volumes taking into account the geometrical complexity of these organelles. Irradiation with 250 keV photons is performed and the lineal energy is calculated. The lineal energy distributions inside the produced phantoms are compared with those calculated inside simple volumes, a sphere and an ellipsoid, where the effect of the shape and volume is clearly seen on lineal energies.